Revisited The Measurement Strategy of Public Sectors Performance Using Fitted Management - Sihombing , Haeryip; M.Y., Yuhazri (UTeM, 2012)
There are no organization of public sector in developing countries can afford to reduce and eliminate the waste resources by an effectively way, especially when the centrally regulated of public service policy is a hindrance to effective delivery of public services in modern globally competitive competitions. Based on this reason, new approaches to making large and complex bureaucratic organizations more responsive to citizens and their needs are required by building on charting the new relationships among officials and the administrators. First, the effectiveness of public should be therefore associated to the policies and programs based on the functions of public services where their roles to become better at achieving what are expected over better service and dignity, as well as to positively affects the workers. Second, the performance related should not be always about the developing of targets, setting measures, and measuring the process but rather to develop the indicators of performance management and understanding the outcome to support the organizational needs. This is means that the measurements of public service organizations need to understand what is required. Based on this background, this paper review the challenges faced by public sector in order to seek for the solutions based on concept integration, implementation, and performance measurement of their business. The proposed conceptual framework is Fitted Management, where the exploration of organization processing capabilities and how to manage it (to be consistent with the globalization) based on the premise of what constitutes a customer value in the public sector by improving the ability of employees and organizations.